Pemodelan Oksigen Terlarut (Dissolved Oxygen/DO) di Perairan Teluk Benoa - Dika Madyawan; I Gede Hendrawan; Yulianto Suteja (Journal of Marine and Aquatic Sciences, 2020)
Dissolved oxygen by definition is the total milligrams of oxygen gas dissolved in water which is influenced by atmospheric pressure, temperature, salinity, water turbulence, photosynthesis, respiration and waste. The Finite Volume Coastal Ocean Model (FVCOM) method is one of the ways to study water quality model. This study is aimed to determine the spatial distribution of DO concentration in Benoa Bay during the rainy season on the water surface and the deeper waters. This study was conducted in the waters of the Benoa Bay and rivers which empties into Benoa Bay on January 29 to February 25 2018, representing the rainy season. In carrying out the simulation, two steps are carried out, firstly numerical modeling was done to get ocean current patterns in Benoa Bay, and secondly making a numerical model where DO concentration values are added to get the results of DO distribution horizontally and vertically. The value of DO results ranged from 4.3 to 8.4 mg/l on the surface water of Benoa Bay. Based on tidal results of model during its highest tide, high tide to low tide, and lowest tide conditions, DO concentrations on the surface are higher than the deeper water. However, during low tide to high tide conditions, DO concentrations on the surface water is higher than the deeper water. Conclusions obtained from this research shows that DO concentrations in Benoa Bay waters have a minimum value of 2 mg/l and a maximum of 8.4 mg/l., where conditions of the tidal elevation affects DO concentrations, where it tends to go higher near the land and on sea surface.